Improve the sleep quality of elderly in nursing home using lavender aromatherapy - Imelisa, Rahmi; Abdullah, Syahla Nabila; Musri; Safarina, Lina; Roswendi, Achmad Setya (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Inadequate sleep and poor quality could interfere with the elderly health. The number of elderly people with sleep quality problems will be much larger, more serious, and more complex. One way to overcome sleep quality is non-pharmacological therapy, one of which using lavender aromatherapy. Objective: This study aimed to determine the effect of lavender aromatherapy to the sleep quality of elderly at a Nursing Home.Methods: This research used a quasy experiment with a purpossive sampling design. Sample 32 elderly was divided into 2 groups, intervention and control groups. Data obtained used a translate of PSQI questionnaire. The intervention groups was given the lavender aromatherapy for 5 days. Data analyzed for the univariate and bivariate used a Mann-Whitney test. Results: Score of sleep quality in the intervention group pretest was 9.13 and posttest was 4.69. The score were decrease approximately 4,44 point. Whereas in the control group pretest was 9.19 and posttest was 8.13. The bivariate analysis for pre and post test data in intervention group revealed that the p-value was 0.001 (<?=0.05).Conclusion: Lavender aromatherapy significantly effect the sleep quality of elderly in a nursing home